Simplified Frame Design of Type PR Construction - Ackroyd, Michael H. (Engineering Journal, 1987)
Design of unbraced building frames using simple connections between beams and columns has been based historically on Type 2 Construction assumptions. Extensive research on the performance of this type of frame has led to the recommendation that Type 2 Construction should be limited to frames less than 10 stories tall, when the lateral load is resisted entirely by the unbraced frame. Moreover, it was shown that the governing limit state in such frames is overall frame instability under combined wind and gravity loads, initiated by extensive plastification of the leeward column stack. Two common features of this limit state are that girders are loaded to about half their bending capacity and the exterior columns are heavily overloaded in bending. The reason for this inappropriate apportionment of steel to the girders and exterior columns is that the simple connections do possess rotational stiffness and tend to decrease the in-span girder gravity moments by developing a fraction of the fixed-end moments, referred to herein as flexible-end moments. This paper describes a more appropriate model for gravity analysis of frames with flexible beam-to-column connections that enables a simplified design procedure for Type PR Construction.